2020
DOI: 10.1002/ejsp.2701
|View full text |Cite
|
Sign up to set email alerts
|

Market mindset impacts moral decisions: The exposure to market relationships makes moral choices more utilitarian by means of proportional thinking

Abstract: We show that exposure to market relationships increases people's tendency to make utilitarian moral choices by means of proportional thinking-the definitional feature of the market mindset. In Experiment 1, participants primed with market relationships made more utilitarian choices in both the trolley and the footbridge dilemmas. In Experiment 2, priming market mindset led to more utilitarian moral choices and to greater focus on the proportion of survivors to victims. Experiment 3 showed that the effect of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 69 publications
2
35
0
Order By: Relevance
“…A meta-analysis of earlier studies on the psychological consequences of being in a market mindset (Gasiorowska & Zaleskiewicz, 2021;Zaleskiewicz et al, 2020) revealed a small effect of such a manipulation (Hedge's g = 0.405). A priori power analysis using G*Power (Faul et al, 2007) revealed that, given an alpha of .05 and a power of .80, a sample of 97 participants per condition would be required to detect such an effect.…”
Section: Methods Participantsmentioning
confidence: 96%
See 2 more Smart Citations
“…A meta-analysis of earlier studies on the psychological consequences of being in a market mindset (Gasiorowska & Zaleskiewicz, 2021;Zaleskiewicz et al, 2020) revealed a small effect of such a manipulation (Hedge's g = 0.405). A priori power analysis using G*Power (Faul et al, 2007) revealed that, given an alpha of .05 and a power of .80, a sample of 97 participants per condition would be required to detect such an effect.…”
Section: Methods Participantsmentioning
confidence: 96%
“…In Experiment 1, we investigated whether a simple visual manipulation of market vs. communal mindset can effectively trigger associations with free-market ideology. We used the manipulation method developed by Zaleskiewicz et al (2020) in their research on the effects of market mindset on moral judgment and choice (see also Gasiorowska & Zaleskiewicz, 2021). In this method, participants are exposed to pictures illustrating different social interactions and asked to consider them for a while.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, helping is in most cases non-contingent-people often support close others without expecting anything in return, which makes such a situation asymmetrical (Clark & Aragón, 2013). Market exchange, however, is symmetrical and proportional in nature: people expect that the input they provide will be repaid not only at a comparable value but also as quickly as possible (Fiske, 1992;Zaleskiewicz et al, 2020). Second, asking for help is related to greater uncertainty, since when people ask for help, they cannot be sure that others will react positively to their request.…”
Section: Is Help Of Others the Only Alternative To A Lack Of Individu...mentioning
confidence: 99%
“…In other words, when people pay for something, they can in most cases expect that their order will be processed effectively, because this is how an efficient market works. Third, being involved in a communal relationship is linked to having the communal mindset, while engaging in a market exchange relationship is connected to having the market mindset (Fiske, 1992;Gasiorowska & Zaleskiewicz, 2021;Zaleskiewicz et al, 2020) or using market cognition (Zaki et al, 2021). The market mindset is also associated with a sense of control and self-efficacy (Gasiorowska et al, 2018).…”
Section: Is Help Of Others the Only Alternative To A Lack Of Individu...mentioning
confidence: 99%